A system dynamic model for measuring the construction quality of buildings' structures - Mehrdad Shokouh-Abdi; Morteza Zahedi; Ahmad Makui (Management Science Letters, 2011)
Abstract: One of the most important issues on quality of building structure is its resistance against earthquake. Earthquake, as one of natural disasters, has been one of the main reasons of fatal incidents in developing countries. Any attempt to increase the quality of building structure could reduce any possible damages an earthquake could cause on society. This paper presents a system dynamic model to study the importance and behavior of the factors which affect the construction quality of buildings' structures. The proposed model of this paper is analyzed for a case study and the results are discussed. The paper also uses DEMATEL technique to compare the results of the proposed method. The paper concludes that among the whole factors which affect the construction quality of buildings' structures, the "performance of related organizations and institutions" is of the most important ones.